USHUL IKHTILAF DALAM PERSOALAN IJTIHADIYYAH PERSPEKTIF IBNU TAIMIYAH (Ahkam: Jurnal Hukum Islam, 2022)
Ikhtilaf in every ummah is a certainty and a blessing for the Muslims. This reality has existed since the best era in the journey of the Islamic Ummah, namely when the period of Prophet and his Blessed-Companions. Ibnu Taimiyah is one of the Islamic thinkers who has many followers as well as opponents in the history of Islamic thought. He has also contributed a lot and concerned about the issue of Ushul Ikhtilaf. This study discusses Usul Ikhtilaf in the view of Ibn Taimiyah and understands his thoughts related to the basic principles of differing opinions. This research is descriptive qualitative. Meanwhile, the data was generated through library research on the works of Ibn Taimiyah, especially the book Majmu' fatawa. This study shows that Ibn Taimiyah has clear principles in addressing differences of opinion on Ijtihadiyah issues. Data collection techniques from this material are carried out thematically. Furthermore, in analyzing the data used content analysis method. This research shows that Ibn Taimiyah has clear and comprehensive principles in dealing with differences of opinion on Ijtihadiyah issues. These principles include 1). Not denying the issue of ijtihadiyyah; 2). It is not permissible to force the results of ijtihad to be followed; 3). It is not justified to boycott fellow Muslims because of different opinion choices; 4). There should be no denial between fellow muqallids; and 5). It is not permissible to disbelieve fellow Muslims just because of mistakes in ijtihad and ta'wil.